A checklist of DPR’s Publications on Flora of Nepal-2 (Non- flowering Plants) - Manandhar, Vidya; Dahal, Sajan; Subedi, Mahendra N. (Journal of Plant Resources, 2008)
Not available Keywords: DPR; flora of Nepal; Museum; Nepal; Japan. Bulletin of the Department of Plant Resources Vol. 30, 2008 pp 109